Extreme site fidelity in long‐distance migratory shorebirds in Australia and potential implications for conservation - Tobias A. Ross; Robyn Atkinson; Maureen Christie; Danny I. Rogers; Chris Hassell; Roz Jessop; Jonathan T. Coleman; Theunis Piersma; Sara Ryding; Aaron Spence; Marcel Klaassen (Conservation Biology, 2026)
Site fidelity is the tendency for animals to repeatedly return to the same locations, either within or between years. Site fidelity enables animals to utilize knowledge of previously visited locations, including assessments of seasonal variations in health and mortality risks (e.g., predation), resource availability, and social benefits such as pairing with previous mates. However, rigidly enacted site fidelity may come with fitness costs in times of rapid habitat change. One group believed to exhibit site fidelity is migratory shorebirds (families Charadriidae and Scolopacidae). Shorebirds that migrate annually via the East Asian–Australasian Flyway have experienced rapid population declines due to habitat loss in Asia. Although high site fidelity may influence these declines under a global change scenario, only limited, species‐specific analyses of site fidelity have been previously conducted. Our study used an extensive dataset of 636,167 records of over 84,000 banded individual shorebirds from 1976 to 2025 to present an overview of site fidelity for 12 migratory shorebird species during their nonbreeding season in Australia. We found overall site fidelity of >95% across 10 out of 12 species, with the only exceptions being red knot ( Calidris canutus ) and sanderling ( Calidris alba ), with movements often limited to sections of coastline less than 20 km long. Juvenile and immature birds were usually less site faithful than adults. The high site fidelities of most species suggest that local site knowledge is of considerable importance and that individuals forced to relocate to alternative sites will likely incur a cost. Our findings also imply that habitat loss may have immediate population‐level consequences through reduced fitness of displaced birds.

Per- and poly-fluoroalkyl substances (PFAS) do not accumulate with age or affect population survival in ruddy turnstone (Arenaria interpres) - Tobias A. Ross; Junjie Zhang; Tonje G. Skaalvik; Robyn Atkinson; Roz Jessop; Alexandros G. Asimakopoulos; Veerle L.B. Jaspers; Marcel Klaassen (Science of The Total Environment, 2024)

Assessment of contaminants, health and survival of migratory shorebirds in natural versus artificial wetlands – The potential of wastewater treatment plants as alternative habitats - Tobias A. Ross; Junjie Zhang; Michelle Wille; Tomasz Maciej Ciesielski; Alexandros G. Asimakopoulos; Prescillia Lemesle; Tonje G. Skaalvik; Robyn Atkinson; Roz Jessop; Veerle L.B. Jaspers; Marcel Klaassen (Science of The Total Environment, 2023)